Urological outcomes in nonagenarians with prostate cancer - White, Josh; Ory, Jesse; Morris, Heather; Rendon, Ricardo A.; Mason, Ross; Cox, Ashley (Canadian Urological Association Journal, 2021)
Introduction: Nonagenarians represent a growing patient population. Herein, we report on the largest cohort of Canadian nonagenarian patients, to our knowledge, with prostate cancer. Methods: A retrospective chart of 44 nonagenarian men diagnosed with localized or metastatic prostate cancer between 2006 and 2019 was performed. Diagnoses were based on pathological specimens or the presence of a high prostate-specific antigen (PSA >20) or abnormal digital rectal exam (DRE) in the setting of metastatic disease on imaging. Patient demographics, presenting complaints, and treatments required were included in the analysis. A descriptive statistical analysis was performed. Results: The median patient age at time of referral was 91.1 years (interquartile range [IQR] 90.2–92.9). The median PSA at time of referral was 54.0 (IQR 18.2–142.6). Metastatic disease was present in 55% of patients at time of diagnosis (n=24). Most patients required at least one urological intervention (n=35). There were 56.8% of patients who received androgen deprivation therapy (ADT) as part of their treatment regime (n=25). Half (50%) of patients were managed with androgen receptor axis-targeted agents (ARAT), as well as ADT (n=22). Five patients (11.4%) underwent surgical castration. Death due to any cause was noted in 52.3% of patients (n=23) throughout the study period, with the median age at death being 94.4 years (IQR 92.3–97.0). Death due to prostate cancer was noted in 18.2% of patients (n=8). Conclusions: This study highlights common presenting complaints for nonagenarian patients with prostate cancer and that many require urological intervention despite advanced age. Future studies should address patient-reported quality-of-life outcomes in the nonagenarian population with prostate cancer.